Death and blintzes : a Belle appleman mystery - Rosen, Dorothy (Academy Chicago Publishers, 1998)
It is the mid-1930s and, in Boston, something not quite kosher is going on at the Classic Clothing Company. Belle Appleman, the young widow recently hired for the Pants department and a long-time devotee of True Detective magazine, jumps at the chance to put her acquired knowledge into practice when the Pants shop steward is murdered. Belle soon learns that "detectiving" can be dangerous, but that doesn't stop her from shooting her questions at everyone from the boss's son's fiancee to the victim's mother.